2015
DOI: 10.1007/s10722-015-0287-6
|View full text |Cite
|
Sign up to set email alerts
|

Special HMW-GSs and their genes of Triticum turgidum subsp. dicoccoides accession D141 and the potential utilization in common wheat

Abstract: High molecular weight glutenin subunits (HMW-GSs) are the critical components of wheat seed storage proteins. They play a crucial role in determining dough viscoelastic properties and end-use quality of wheat flour. To investigate the potential utilization of the special HMW-GSs from wild emmer wheat (2n = 4x = 28, AABB) accession D141 in common wheat (2n = 6x = 42, AABBDD), continued to our previous report of the 1Ay and its coding sequence, the other three HMW-GSs, 1Ax, 1Bx13.1 and 1By16.1, and their coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…It is sometimes possible to recover the original yield by subsequent genetic manipulation, such as backcrossing of lines with alien Glu alleles [ 53 , 54 ]. In our previous study, we revealed that the wild emmer HMW-GSs were detected in F 1 and F 2 offspring of the interspecies hybridization between common wheat and wild emmer [ 55 ]. In the current study, our strategy was to continuously select those single plants with desirable agronomic, high yield, and resistance properties for self-crossing.…”
Section: Discussionmentioning
confidence: 99%
“…It is sometimes possible to recover the original yield by subsequent genetic manipulation, such as backcrossing of lines with alien Glu alleles [ 53 , 54 ]. In our previous study, we revealed that the wild emmer HMW-GSs were detected in F 1 and F 2 offspring of the interspecies hybridization between common wheat and wild emmer [ 55 ]. In the current study, our strategy was to continuously select those single plants with desirable agronomic, high yield, and resistance properties for self-crossing.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 In addition, research has revealed that increased length of repetitive domain, a number of cysteine residues and coils would benefit the formation of gluten polymer. 22,[29][30][31] Protein secondary structure prediction of HMWGAx demonstrates that the number of the α-helixes and their position is similar to the good flour quality Ax1type HMW glutenin subunit. Moreover, HMWGAx protein contained 34% of glutamine residues, indicating the capacity to form inter-chain hydrogen bonds that could provide the elasticity for the dough.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Gli2-AT-107 contained the highest ratio of amino acid residues, which further generated the secondary structures, implying that this gene could be favorable for constructing a good gluten structure and exhibiting superior dough quality. 40,41 Based on such recognition, the quantity and distribution of the 4 toxic epitopes could be applied to associate α-gliadins with a specific chromosome. 13,15 To be specific, the α-gliadins from chromosome 6B were identified free of any intact T cell epitopes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These α-gliadin genes may be exploited as potential resources for decreasing and preventing celiac diseases. In addition, Gli2-AT-107 contained the highest ratio of amino acid residues, which further generated the secondary structures, implying that this gene could be favorable for constructing a good gluten structure and exhibiting superior dough quality. , …”
Section: Discussionmentioning
confidence: 99%